Genome-wide molecular fingerprinting reveals local geographical genetic patterns in the North American angiosperm genus Triosteum (Caprifoliaceae) - Tom Ruttink; Bryan Connolly; Kurt Lamour; Jonathan Hulvey; Yves Bawin; Erin C. Hilley; Peter Tandy (PLoS ONE, 2025)
Triosteum (Caprifoliaceae) is a genus of herbaceous perennial angiosperms composed of three Asian and three North American species. The range of two similar species, T. aurantiacum and T. perfoliatum, overlap in the state of Massachusetts, USA, where the latter species is considered locally endangered and protected by regulations. The population occurring in Barnstable Co. MA, USA was morphologically atypical and had intermediate characteristics between the two taxa. Genome-wide molecular fingerprinting was used to identify this population by comparison to nearby populations with typical morphology for each of the reference species T. aurantiacum and T. perfoliatum. A set of 220,518 high quality SNPs were used to calculate expected heterozygosity, FIS, nucleotide diversity, and FST, and to create short multi-allelic haplotype markers. Detailed population characterization was performed using Principal Component Analysis (PCA) and fastSTRUCTURE analysis on SNPs, and the haplotype markers were used to create a NJ phylogenetic tree, and pairwise comparisons of the genetic distance (Jaccard Inverse Distance) between individual plants within and between subpopulations, populations, and species. Furthermore, complete chloroplast genome sequences were created, and structural polymorphisms characterized and compared to a range of closely related species. Taken together, the data reveals a fine subpopulation structure within the morphologically atypical population at Barnstable Co. MA, that are more closely related to T. perfoliatum than to T. aurantiacum.